Let $f$ and $g$ be two functions in $x$, where $x$ ∈ ℝ, then:

1. $(f±g)(x) = f(x) ± g(x)$

2. $a(f(x)) = af(x)$, $a$ ∈ ℝ

3. $(fg)(x) = f(x)g(x)$

4. $(f/g)(x) = {f(x)}/{g(x)}$, $g(x)$ ≠ 0

The composition of two functions, g and h, such that g is applied first and h second, is given by:

(g ^{o} h)(x) = g(h(x))

The domain of the composite function (g ^{o} h) is the set of all x in the domain of h such that h(x) is in the domain of g.

Example

e.g. Let f(x) = √x, and g(x) = $x^2$. (f (g |
e.g. Let $f(x) = √{x+4}$, and g(x) = $x^2$. (f (g |

From these examples, we can see that (f ^{o} g)(x) is not always equal to (g ^{o} f)(x)!

The function that is applied first is the 'inside' function, and that applied second the 'outside' function. e.g. in $f(x) = (x+3)^2 = (g(h(x))$, the inside function is $h(x) = x+3$, and the outside function is $g(x) = x^2$.

If x is in the domain of the composite function (g ^{o} h), then x must be in the domain of h, and h(x) must be in the domain of g.

The inverse of a function $f(x)$ is written as $f^{-1}$. The effect of the inverse of a function is to reverse the action of the function: if x undergoes a transformation to y through function $f(x)$, then applying $f^{-1}(x)$ to y will return the original value of x.

For example, if $f(x) = 2x + 4$, then $f^{-1}(x) = {x - 4}/2$.

Not all functions have an inverse. Be careful, $f^{-1}(x)$ is not the same as $[f(x)]^{-1}$. $f^{-1}(x)$ is a reflection across the line $y = x$, and $[f(x)]^{-1}$ is a reflection across the x-axis.

Functions that do not have an inverse can be tested by the horizontal line test.

If any horizontal line crosses the graph of a function more than once, then the function has no inverse. This is because the inverse is not a function, but a relation (2 values of y for one value of x.

An example of a function that has no inverse is $f(x) = x^2$, while $f(x) = x^3$ does have an inverse.

If $f(x) = 4x - 6$, the inverse can be found by setting y as $f(x)$, then exchanging the places of x and y:

$y = 4x - 6$, so $x = 4y - 6$ for the inverse.

Rearranging to return y to the left:

$y = {x + 6}/4$

This can be written as the inverse: $f^{-1}(x) = {x + 6}/4$

To check that a function is the inverse of another function, combine the functions:

$$(f o f^{-1})(x) = x$$Example above: $(f o f^{-1})(x) = 4({x + 6}/4) - 6 = x$

A self-inverse function is a function whose inverse is the same. e.g. $f(x) = a/x$ and $f(x) = a - x$, where a ∈ ℝ.

where $I(x) = x$. The identity function leaves $x$ unchanged.

Content © Renewable-Media.com. All rights reserved. Created : September 26, 2014 Last updated :July 20, 2015

The most recent article is:

View this item in the topic:

and many more articles in the subject:

Physics is the science of the very small and the very large. Learn about Isaac Newton, who gave us the laws of motion and optics, and Albert Einstein, who explained the relativity of all things, as well as catch up on all the latest news about Physics, on ScienceLibrary.info.

1800 - 1860

Charles Goodyear is a model of the determined inventor, who struggled to find the secret to a better rubber, despite years of financial hardship and frustration.

Website © renewable-media.com | Designed by: Andrew Bone